Synthesis, structures, electrochemical studies and antioxidant activities of cis-dioxomolybdenum(VI) complexes of the new bisthiocarbohydrazones - KOCA, ATIF (ELSEVIER SCIENCE BV, 2015)
Potentially pentadentate ONSNO donor new Schiff bases were prepared by the condensation of thiocarbodihydrazide with 3,5-dibromosalicylaldehyde (H3L1), 3-bromo-5-chlorosalicy-laldehyde (H3L2) and 3,5-dichlorosalicylaldehyde (H3L3). The reactions between his (acetylacetonato) dioxomolybdenum(VI) and Schiff bases in the presence of donor solvents yielded neutral cis-dioxomolybdenum(VI) complexes with the general formula [MoO2HL(D)] (HL = tridentate ONS donor Schiff base ligand; HL1, HL2, HL3) and D = methanol, ethanol, dimethyl sulfoxide, dimethylformamide, pyridine). All the compounds were characterized by elemental analysis, UV, IR, H-1 NMR spectroscopies. The thermal properties of the complexes were also investigated by thermogravimetry technique and the thermal behavior depending on the second ligand molecule was discussed. The synthesized compounds were screened for their antioxidant capacity by using the cupric reducing antioxidant capacity (CUPRAC) method. In addition, electrochemical behaviors of the complexes were studied using cyclic voltammetry and square wave voltammetry. Half wave potentials (E-1/2) are significantly influenced with the central metal ions, but slightly influenced with the nature of substituents on thiocarbohydrazone ligands. In situ spectroelectrochemical studies were employed to determine the spectra of electrogenerated species of the complexes and to assign the redox processes. The fluorescence properties of the bisthiocarbohydrazone ligands and their dioxomolybdenum(VI) complexes in DMSO solutions were investigated. (C) 2015 Published by Elsevier B.V.
Keywords: Dioxomolybdenum(VI); Thiocarbohydrazone Schiff bases; Spectroscopy; Cyclic voltametry; Antioxidant; MOLYBDENUM(VI) COMPLEXES; CRYSTAL-STRUCTURE; METAL-COMPLEXES; DONOR LIGANDS; ACTIVE-SITES; THIOCARBOHYDRAZIDE; SALICYLALDEHYDE; CARBOHYDRAZIDE; REDUCTION